Moderasi Beragama di Indonesia dalam Perspektif Persekutuan Allah Tritunggal Menurut Leonardo Boff - Jie, Marcelino Bramantyoko (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
This study discusses religious moderation in Indonesia from the perspective of the Triune God according to Leonardo Boff. The contribution of this study is the contribution of the values of the Triune God according to Leonardo Boff for religious moderation in a pluralistic Indonesia. This study is a qualitative descriptive and utilizes a literature review method on religious moderation and Leonardo Boff’s books. This study finds that the Triune God according to Boff can be a model or inspiration for religious moderation in Indonesia today. Boff describes the communion of the Triune God with the terminology of perichoresis which describes the meaning of dwelling together, being together, and permeating each other between the Divine Persons of the Triune God. Perichoresis can be applied to the values of religious moderation that reflect brotherly relations, teach everyone to respect the differences between each other, heed the attitude of sharing feelings, justice for minorities and the majority, and uphold tolerance. This fellowship also invites others to unite with Him, which is relevant to Indonesia’s motto, Bhinneka Tunggal Ika.